(untitled) (Journal of Food and Dietetics Research, 2025)
This paper discusses how nutrition-related topics are represented in textbooks used by the primary school-going children of the government schools of Khyber Pakhtunkhwa (KP), Pakistan. Recognizing the important role nutrition education plays in promoting healthy lifestyles and preventing malnutrition, this study aims to evaluate the adequacy, accuracy, and integration of nutrition-related concepts within the school curriculum. A qualitative content analysis was done on textbooks of key subjects Science, Mathematics, Social Studies, and Urdu across Grades 1 to 5. The content analysis was to identify the coverage of essential topics on nutrition including food groups, essential nutrients, hygiene, malnutrition, and dietary habits, and assess the systematic introduction and reinforcement of the concepts across various grade levels and subjects. Results suggest that while concepts of basic nutrition are well integrated into the curriculum, gaps lie in the aspects of depth, consistency, and practical application. The most serious issues identified were the low inclusion of micronutrients and malnutrition; subject integration is broken up, interaction and real-life applications are weak, and content is not adequately contextualized in relation to local dietary practices. These gaps reduce the effectiveness of nutrition education in equipping students with the knowledge and skills necessary to make informed dietary choices. This study underscores the need for curriculum improvements to ensure a more comprehensive and structured approach to nutrition education. It suggests greater interdisciplinary integration, inclusion of practical learning activities, and incorporation of culturally relevant dietary examples to enhance students’ understanding and application of nutrition knowledge. Improving nutrition education at the primary level can be beneficial in the long run to address malnutrition and improve dietary habits among the future generations in KP.